Murai Batu's (Copsychus malabaricus) Peak Frequency Sound: The Impact toward Stomatal Pores of The Cayenne Pepper (Capsicum frutescens L) Leaves - Sobiatin, Eka; Herianto, Herianto; Khosiyatun, Nur; Fatharani, Mirra; Kuswanto, Heru (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
Cayenne pepper (Capsicum frutescens L) is one of Indonesian most favorite chili called cabai rawit while Murai Batu (Copsychus malabaricus) is one of the Indonesian bird which has a distinctive sound. This bird is widely found in the territory of Indonesia, therefore, it is exciting to combine cayenne pepper and Murai Batu into a study. This study aims to determine the effect of Murai Batu's sound toward stomatal pores of the cayenne pepper leaves. Two months old cayenne was used in this study. The sound of Murai Batu was obtained by directly recording it using a recording device. The sound recorded was then inserted into the sound analyzer software. The recording of Murai Batu's sound was exposed to the cayenne pepper plant, particularly its leaves. The stomatal pores area of cayenne leaves were observed under a computer-connected microscope. The results of the study show that Murai Batu's sound affects the area of the stomatal pores. The benefit of this study is to provide information regarding the potential of the Murai Batu's sound to increase the photosynthesis process of cayenne leaves by looking at the sound effects of birds' chirping on the stomatal pores leaves the area.